Front-End Internship Journal: Enhancing UI and Implementing User Analytics with Reactjs and Chartjs in Property Business Admin Portal - wiratmaja, yumna; atmadiputra, pradana; normalisa (Liaison Journal of Engineering, 2024)
This paper presents an overview of the author's internship experience at Astra Property, focusing on front-end development tasks undertaken within the admin portal project. The author discusses the practical application of software engineering principles and methodologies, with a particular emphasis on agile methodology facilitated by Jira software utilising Kanban methods. Tasks executed during the internship include refining sorting systems, implementing advanced features such as the Daily Active Users dashboard using Chart.js, and collaborating with colleagues to optimise user interface design. Through a systematic approach to project management and iterative development processes, the author has produced an enhanced user experience through design revamp and improved task efficiency with quick links applied. This experience serves to deepen the author's understanding of front-end development practices and underscores the importance of continuous learning and adaptation in the software engineering domain. Keywords: Agile Methodology, Admin Portal, Reactjs, Ant Design, Chartjs